Gluteal compartment syndrome caused by traumatic rupture of the superior gluteal artery - Djemil Omerović; Ismet Gavrankapetanović; Faris Gavrankapetanović; Amel Hadžimehmedagić; Faruk Lazović; Amir Ahmetović (Биомедицинска истраживања, 2016)
Introduction: We report a case of a sixty-year-old man diagnosed with glutealcompartment syndrome caused by traumatic rupture of the superior glutealartery associated with fracture of the inferior pubic ramus and blunt trauma.Case report. A patient was injured falling from a height of four meters. Signsof compartment syndrome and sciatic nerve compression developed threehours after the injury. The patient went through a computerized tomography(CT) scan procedure with contrast, which showed a hematoma in the glutealregion, but without signs of active bleeding. However, after observation andmonitoring of the patient, CT angiography was performed which revealeda rupture of the superior gluteal artery. Fasciotomy and debridement wereperformed and the patient was diagnosed with gluteal compartment syndromeand rupture of the superior gluteal artery. Surgery resulted in a significantimprovement of the patient’s condition. Conclusion: Traumatic gluteal compartment syndrome is a rare condition.Gluteal compartment syndrome should be taken into consideration in eachpatient with pelvic trauma and hematoma in the gluteal region whose neurologicalstatus is affected. Prompt diagnosis and fasciotomy are crucial inthe treatment and fasciotomy presents the gold standard in the treatment.
Keywords: gluteal compartment syndrome; pelvic trauma; superior gluteal artery rupture; sciatic nerve compression